RANCANG BANGUN ALAT KONTROL DAN MONITORING SISTEM PENYIRAMAN, PEMUPUKAN, DAN PENCEGAHAN HAMA BERCAK DAUN PADA PEMBIBITAN KELAPA SAWIT BERBASIS IOT - Darmawan, Riski; Attirmidzi, Hazipah; Saputra, Zanu; Yudhi, Yudhi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Oil palm is one of the most important crops in Indonesia's plantation industry. In terms of cultivating oil palm, farmers still rely on manual-based systems, such as watering, fertilizing, and applying pesticides. With this tool, it is expected to increase efficiency in managing watering, fertilizing, and applying pesticides to oil palm seedlings, and farmers can monitor pH levels, soil moisture, and weather conditions in real time on the blynk application. This system consists of several main components, namely ESP-32 as a microcontroller hardware and software component. The sensors used are soil moisture sensor, raindrop sensor, and pH sensor. The soil moisture sensor is used to measure the level of soil moisture around the roots of oil palm seedlings. The rainfall sensor will provide information whether it is raining or not. The pH sensor measures the acidity level. Data from the three sensors will be sent in real-time to the IoT platform, namely the blynk application via a wireless network in the form of WiFi. Based on the research results, it can be seen that this tool can measure soil pH levels with a fairly low average error value of 0.0354%. The soil moisture sensor can also measure the soil moisture level with precision according to the actual data. Tests were carried out with three soil samples and tested three times.